Medical students' understanding of oral and maxillofacial surgery: an Irish perspective. Issue 4 (May 2017) - Kielty, P.G.C.; O'Connor, B.R.; Cotter, C.J.; Goodson, A.M.C.; Payne, K.F.B.; Tahim, A.
Abstract: Oral and Maxillofacial Surgery (OMFS) remains an enigmatic specialty in Irish medicine and many students are unaware of its scope and the unique career pathway involved. We completed a multicentre cross-sectional study to identify their ability to identify the requirements for entry to specialty training year 3 (ST3) in OMFS, to assess their awareness of OMFS surgeons, and their general awareness of, and exposure to, the specialty. Data were collected through an electronic questionnaire. Participants were asked to select the most suitable surgical specialty to treat a number of common conditions in the head and neck, and to choose the requirements they deemed essential for specialist training. Knowledge was measured by the number of correct responses. A total of 443 medical students participated (University College Cork (UCC) n = 328, 74%; Royal College of Surgeons in Ireland (RCSI) n = 113, 26%). A total of 318/374 (85%) had had no previous experience of OMFS, 38/374 (10%) had had theoretical teaching only, and 18/374 (5%) had had clinical experience. A total of 212/329 (64%) wished for greater exposure as a student, but only 34/329 (9%) would consider a career in the specialty. The median (IQR) number of correct responses for OMFS procedures was 3.0/10 (2.0), with women, direct entrants, and RCSI students scoring highest. Only 11/367 (3%) could identify the minimum entry requirements for a post of specialist registrar. This study has identified a potential gap in the undergraduate curriculum. Although medical students are rarely taught about OMFS, they show an interest in learning more.